Pola Komunikasi Mahasiswa dengan Dosen dalam Melakukan Diskusi pada Perkuliahan Melalui Website - Farsha Ahdyra Islamia; Aning Sofyan (UNISBA Press, 2023)
Abstract. Since the emergence of the pandemic, communication and lectures conducted by students and lecturers have been limited, so all lecture discussion activities must be carried out in each other’s house. However, with the development of new media and nowadays increasingly sophisticated technology, the learning system can also be carried out asynchronously where lecturers can use e-learning media for the learning process. It's the same with the Unisba campus which carries out learning through e-learning on the website ekuliah.unisba.ac.id. With an online learning system, there are also communication patterns that occur in lecture discussions via websites between students and lecturers. So the researchers want to dig deeper into the communication patterns of students and lecturers through e-classes. The purpose of conducting this research is to find out the motives, experiences, and meanings of e-class users in conducting lecture discussions. The results of this study are the motives of communicators in using e-college as a means of discussion, namely tending to formal/instrumental communication motives and social communication motives, the results of experience show positive values obtained by lecturers or students, namely the existence of flexible learning time, and for negative values that are obtained are linear communication patterns, language barriers, and technical constraints. Then the meaning of the communication patterns that occur between students and lecturers are secondary communication patterns and circular communication patterns that make this meaningful and also linear communication patterns that make communication meaningless. The method used in this study is a qualitative method with a phenomenological study approach which is also supported by the CMC (Computer Mediated Communication) theoretical concept. Abstrak. Semenjak munculnya pandemi komunikasi dan pembelajaran perkuliahan yang dilakukan oleh mahasiswa maupun dosen terbatas sehingga harus dilaksanakan seluruh kegiatan diskusi perkuliahan di rumah masing-masing. Namun dengan adanya perkembangan media baru dan teknologi zaman sekarang yang sudah semakin canggih maka sistem belajar dapat dilakukan secara asynchronous dimana dosen dapat menggunakan media e-learning untuk proses pembelajaran. Sama dengan kampus Unisba yang melaksanakan pembelajaran melalui website ekuliah.unisba.ac.id. Dengan adanya sistem pembelajaran secara daring maka ada pula pola komunikasi yang terjadi di dalam diskusi perkuliahan melalui website antara mahasiswa dengan dosen. Maka peneliti ingin menggali lebih dalam lagi terkait pola komunikasi mahasiswa dengan dosen melalui e-kuliah. Tujuan dilakukannya penelitian ini adalah untuk mengetahui bagaimana motif, pengalaman, dan juga makna dari para pengguna e-kuliah dalam melakukan diskusi perkuliahan. Hasil dari penelitian ini adalah motif pelaku komunikasi dalam menggunakan e-kuliah sebagai sarana diskusi yaitu cenderung kepada motif komunikasi formal/instrumental dan motif komunikasi sosial, hasil pengalaman terdapat nilai positif diperoleh dosen atau mahasiswa yaitu adanya waktu pembelajaran yang fleksibel, dan untuk nilai negatif yang diperoleh adalah pola komunikasi linear, kendala bahasa, dan kendala teknis. Lalu makna dari pola komunikasi yang terjadi antara mahasiswa dengan dosen adalah pola komunikasi sekunder dan pola komunikasi sirkular yang menjadikan ini bermakna dan juga pola komunikasi linear yang menjadikan komunikasi tidak bermakna. Metode yang digunakan yaitu menggunakan metode kualitatif dengan pendekatan studi fenomenologi yang didukung juga oleh konsep teori CMC (Computer Mediated Communication).